High Throughput Omnidirectional Printing of Tubular Microstructures from Elastomeric Polymers (Adv. Healthcare Mater. 23/2022). Issue 23 (8th December 2022) - Liu, Chuan; Campbell, Scott B.; Li, Jianzhao; Bannerman, Dawn; Pascual‐Gil, Simon; Kieda, Jennifer; Wu, Qinghua; Herman, Peter R.; Radisic, Milica
Abstract : Biomimicking In article 2201346 by Milica Radisic and co‐workers, scaffolds fabricated by coaxial printing of bioelastomers can mimic both the structures and mechanical properties of native tissues, which are ideal for organ‐on‐a‐chip and tissue engineering applications. This image shows an artistic tubular structure made of a biodegradable elastomer called PICO.